A Randomized Controlled Trial of Right Low Frequency rTMS Combined with Escitalopram in Treatment of Patients with Firstepisode Depression in General Hospitals. Issue 5 (2017) - Yang, Hui; Zhang, Maolan; Xiang, Hui; Qin, Qing; Huang, Ying; Yang, Zhenggui
No abstract available